Decision-making in interhospital transfer of traumatic brain injury patients: exploring the perspectives of surgeons at general hospitals and neurosurgeons at neurotrauma centres - Mathias Cuevas-Østrem; Torben Wisborg; Olav Røise; Eirik Helseth; Elisabeth Jeppesen (BMC Health Services Research)
Abstract Background Traumatic brain injury (TBI) is a significant public health concern. Advancing age and comorbidities are associated with a reduced probability of being transferred to neurotrauma centres (NTCs) from non-neurosurgical acute care trauma hospitals (ACTHs). However, the extent to which these decisions reflect well-considered treatment-limiting decisions and which influence other factors have on the decision-making process remains unclear. Objective To increase the understanding of adults’ access to NTC care by exploring the decision-making process for interhospital transfer of patients with isolated TBI, elucidating factors influencing these decisions. Methods Fifteen surgeons and neurosurgeons from four hospitals in Norway were recruited through purposive sampling to four semi-structured focus group interviews. Surgeons represented ACTHs and neurosurgeons NTCs, and all participants were responsible for TBI patients' initial care and transfer decisions. Interviews were thematically analysed. Results We identified several factors influencing transfer decisions, captured in six main themes under one overarching theme; ‘The chance of a favourable outcome’. The six main themes reflect surgeons’ and neurosurgeons’ decision-making process, which included clinical and system-level factors: (A) ‘Establish TBI severity: Glasgow Coma Scale score and head CT’, (B) ‘Preinjury health status: comorbidity, functioning, and age’, (C) ‘Distance from ACTH to NTC: distance is time and time is brain’, (D) ‘Uncertainty and insecurity’, (E) ‘Capacity at NTC’, and (F) ‘Next of kin involvement’. Conclusion On-call surgeons and neurosurgeons responsible for making transfer decisions for TBI patients emphasise the importance of patient-centred decisions, including individual patients’ risk factors and overall health status.